Subdural empyema caused by Aggregatibacter segnis: a rare case report and literature review - Qinghua Li; Xiaotong Fan; Kailiang Wang; Xiaolong Wu; Junjie Li; Yang An; Penghu Wei; Wenli Shi; Yongzhi Shan; Sichang Chen; Guoguang Zhao (BMC Infectious Diseases)
Abstract Background Aggregatibacter species are Gram-negative bacteria typically recognized as oral saprophytes in humans, with invasive infections uncommon in immunocompetent individuals. To the best our knowledge, this is the first reported case of subdural empyema attributed to Aggregatibacter segnis (A. segnis). Case presentation A 50-year-old female was transferred to our hospital from a local facility due to headache, fever, and left-sided limb numbness. Initially suspected of subdural hematoma and viral encephalitis, she did not respond well to prior treatment. Cerebral computed tomography and magnetic resonance imaging revealed a subdural lesion in the frontal-temporal region and sinusitis. Virus-related tests, smear, and culture of cerebrospinal fluid (CSF) were negative. Craniotomy was performed to evacuate the subdual empyema, and A. segnis was detected in the culture of pus. The discrepancy between metagenomic next-generation sequencing (mNGS) and culture highlights diagnostic challenges in this pretreated patient. Antibiotic treatment was guided by culture results and mNGS. Clinical symptoms resolved gradually following surgery and administration of antibiotics. Conclusions This rare case suggested that A. segnis should be considered in the diagnosis of subdural empyema. Multimodal diagnostics, prompt neurosurgical management, and individualized antimicrobial stewardship are crucial in managing rare central nervous system infections.